Development of a Decision Support System Based on the Weighted Product to Optimize Production Scheduling in the Furniture Industry - Yessi Nasia Ulfia; Dian Eko Hari Purnomo; Fesa Putra Kristianto; Julia Dewi Ma’rifah; Taukhid Wisnu Broto; Fitri Indah Puspitaningsih (G-Tech: Jurnal Teknologi Terapan, 2025)
The furniture industry plays a crucial role in Indonesia’s manufacturing sector, which contributed 18.98% to the national GDP in 2024 with a growth rate of 4.43%. However, increasing market demand and product variety have created significant challenges in achieving efficient and timely production scheduling. Inefficient manual scheduling processes have been shown to cause substantial delays, with approximately 31% of production orders experiencing lateness due to poor scheduling and machine utilization. This study aims to design and implement a Decision Support System (DSS) based on the Weighted Product (WP) method to objectively determine production scheduling priorities using order quantity, processing time, and profit value as key criteria. The DSS was developed using Microsoft Visual Basic 6.0 and Microsoft Office Access 2016, utilizing secondary data from a furniture manufacturing company. Validation results show that the DSS achieved a 99.998% accuracy rate compared to manual Excel calculations, indicating correct implementation of the WP computational algorithm. The system effectively enhances production planning by providing objective, data-driven scheduling recommendations, reducing delays, optimizing resource utilization, and improving operational efficiency. Overall, the DSS serves as an effective managerial tool to support decision-making consistency and competitiveness in the manufacturing industry.